Penerapan Asesmen Diagnostik dalam Identifikasi Kesulitan Membaca Siswa Kelas 1 Madrasah Ibtidaiyah Nurul Iman Jombang - Siti Yatimah; Arisni Kholifatu Amalia Shofiani; Eko Hardinanto (Institut Nalanda, 2026)
Early reading ability is a fundamental skill that serves as a key determinant of students’ academic success at the Madrasah Ibtidaiyah level. The main problem identified at MI Nurul Iman Jombang was the significant gap in literacy skills at the beginning of the academic year, where several students were unable to recognize basic sound symbols. This study aimed to comprehensively describe the implementation of diagnostic assessment as an early detection strategy for reading difficulties among first-grade students. Using a qualitative descriptive approach with a case study design, this research involved 28 students as the main subjects. Data were collected through cognitive assessment instruments measuring five indicators (letter recognition, syllable sounds, word reading, sentence fluency, and basic comprehension) as well as non-cognitive assessments covering students’ interest profiles and home environmental support. The findings revealed that the cognitive diagnostic assessment successfully mapped students’ abilities into three groups: proficient group (25%), developing group (40%), and group requiring special intervention (35%). The most dominant difficulties identified were obstacles in pronouncing syllables consisting of three or more letters and visual confusion regarding letters with similar geometric shapes. From a non-cognitive perspective, the study found a literacy paradox in which 89% of students stated that they highly enjoyed reading activities, yet 51% of them did not have consistent reading routines within their families. External factors such as limited parental assistance and unstructured use of digital devices became the primary inhibiting factors. The implication of this study highlights the importance of designing differentiated learning based on diagnostic data to mitigate the risk of functional illiteracy. This study concludes that the systematic integration of diagnostic assessment at the beginning of the semester enables teachers to provide more precise interventions, thereby optimizing the achievement of reading proficiency targets in lower grades in accordance with the mandate of the Merdeka Curriculum.